Eksistensi Pengadilan Pajak Dalam Penyelesaian Sengketa Pajak - I Wayan Sentana Gotama; Ida Ayu Putu Widiati; I Putu Gede Seputra (Jurnal Analogi Hukum, 2020)
Abstract—Tax is one of the sources of state revenue for national development, the collection of which can be imposed based on legislation. In practice, there are often differences in interpretation between tax authorities and taxpayers in understanding the laws and regulations that can lead to tax disputes. As for the formulation of the problem in this study: how is the position of the Tax Court in Indonesia? What constraints hamper the tax dispute resolution process in the Tax Court? This research is expected to expand public legal knowledge, especially regarding the tax court and the realization of a professional, independent and trusted Tax Court. This research is normative research with conceptual approach and legislation. Based on the results of the study, it can be concluded that: 1) The position of the Tax Court is in two (2) institutions, namely technical-judicial guidance by the Supreme Court and organizational, financial, and administrative guidance by the Ministry of Finance. This dualism has caused many parties to doubt the independence and independence of the Tax Court. 2) Constraints in the tax dispute resolution process in the Tax Court are the place of residence of the Tax Court which only exists in the Capital of the State and there are administrative sanctions in the form of fines of 100% (one hundred percent) if the taxpayer's appeal is partially granted or rejected.